A practical approach to section 24C allowances in future expenditure on contracts - Ngema, Ntokozo (My University, 2021)
Section 24C of the South African Income Tax Act 58 of 1962 allows for a deduction against a taxpayer’s income, where the income was received under a contract and the taxpayer, in fulfilling that contract, would be required to finance future expenditure. The purpose of the section is to match the revenue and expenditure within a specific tax year of assessment. Revenue received in advance is taxable when it is received however if the taxpayer is required to incur expenditure against that revenue, they can make use of the provisions of section 24C and get a deduction against that revenue for the future expenditure. Recent court judgments suggest that taxpayers are incorrectly applying the provisions of section 24C. The courts have found in favour of the South African Revenue Service on at least two occasions recently. This study will look at the provisions of section 24C as well as the pitfalls that South African taxpayers ought to avoid when applying this section
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Commerce (Specialising in Taxation), 2021
Keywords: UCTD; Revenue received in advance; Future expenditure; Contract; Interpretation Note no 78; FRS 15; Contractors; SDG-8: Decent work and economic growth